Dinâmica do perfil hematológico e bioquímico dos pacientes com dengue internados no Hospital São José de Doenças Infecciosas em Fortaleza–Ceará no período de janeiro a maio de 2008 - Azin, Francisca Raimunda Felizardo Guerreiro (2010)
This is an observational, descriptive and retrospective study of 154 patients who have been diagnosed clinically and serologically for dengue fever, interned in a tertiary public hospital in the city of Fortaleza of Ceará State, during the period of January – May, 2008, for the purpose of correlating the laboratory examinations, symptoms and alarming signs with the chronological evolution of the disease and to observe the frequencies of the more severe clinical forms of disease, so as to help adopt therapeutic conducts that are more effective. The patients’ ages varied from two to 85 years. The study sample was divided in to two groups: patients < 15 years (n=66) and those ≥15 years (n=88). As the patients were all from a tertiary public hospital, the clinical classification of cases showed that hemorrhagic dengue fever (HDF) was predominant (58.4%), followed by severe dengue (SD – 28.6%) and classic dengue (CD - 13%). The CD patients showed alterations in the laboratory findings such as thrombocitopenia and rise of transaminases, which motivated their hospitalization. The principal laboratory alterations found in HDF patients were: thrombocytopenia, hemoconcentration and rise of transaminases. Similar alternations were found in SD patients, but hemoconcentration was not detected in them. The alarming signs were observed more frequently in the two severe forms of dengue. In the <15-years and ≥15-year groups, the respective clinical pictures were: hemorrhagic manifestations – 55, 55% and 69,23%; acute and continuous abdominal pain – 72,22% and 65,38%; and postural dizziness – 11,11% and 23,08%; vomiting – 61,10% and 38,40%. In the HDF patients, in the <15-years and ≥15-year subgroups, the respective hemorrhagic manifestations were: 52,27% and 65,22%; acute and continuous abdominal pain – 97,73% and 71,74%; and postural dizziness – 9,09% and 43,48%; vomiting –81,80% and 58,70%. Within the chronologic evolution of the disease, these results were important and were independent of the clinical form of the disease and the age group of the patients. In the majority of cases, the laboratory alterations were observed from the 3rd day onwards, being more evident on the 5th day and stabilizing to normal values by the 11th day. Within this chronology, the detection of alarming signs was important for the clinical characterization of HDF and SD cases in patients. These results appear to be relevant for the evaluation of the clinical disease, as the detection of the alarming signs within the chronologic evolution may be utilized as warning signals for the more severe forms of the disease, and hence could help in the early adoption of more efficient therapeutic strategies for the patients.